2019
DOI: 10.3390/w11020240
|View full text |Cite
|
Sign up to set email alerts
|

Water Infiltration and Surface Runoff in Steep Clayey Soils of Olive Groves under Different Management Practices

Abstract: When olive groves are cultivated on clayey soils with steep gradients, as in many Mediterranean areas, reducing the runoff and soil erosion rates by adopting proper soil management practices is imperative. A soil cover by pruning residues may represent an alternative to the commonly adopted mechanical tillage. This study evaluates the water infiltration rates and surface runoff volumes in a steep and clayey olive grove of Southern Italy. These hydrological variables are measured at the plot scale under four so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…The final infiltration intensities were lower under seedbed conditions and increased by one order of magnitude under stubble conditions, or almost decreased to zero for Chernozem. Bombino et al [16] also observed a considerable decrease in the final infiltration due to cultivation on clay soils. Effective infiltration is highly affected by the formation of a surface crust and sealing [45], as the surface is flat and the sediment deposits within a few decimeters.…”
Section: Results Of Infiltration Measurementsmentioning
confidence: 90%
See 1 more Smart Citation
“…The final infiltration intensities were lower under seedbed conditions and increased by one order of magnitude under stubble conditions, or almost decreased to zero for Chernozem. Bombino et al [16] also observed a considerable decrease in the final infiltration due to cultivation on clay soils. Effective infiltration is highly affected by the formation of a surface crust and sealing [45], as the surface is flat and the sediment deposits within a few decimeters.…”
Section: Results Of Infiltration Measurementsmentioning
confidence: 90%
“…Theoretically, smart technologies can change the amount and intensity of artificial precipitation in space, depending on the current soil properties, such as infiltration. In practice, further measurements for calibration and validation are required to ensure successful and stable application [16].…”
Section: Introductionmentioning
confidence: 99%
“…Compacted soil layers have less pore space and limit water movement through the soil profile [35]. A soil covered by vegetation increases infiltration and reduces runoff [36].…”
Section: Discussionmentioning
confidence: 99%
“…They conclude that the limiting factor to calibrate and apply such modeling tools is not in the theoretical part, but it is rather the lack of soil structural and hydrologic data. Bombino et al [15] analyzed some hydrological processes, namely, water infiltration and surface runoff at the plot scale on a steep slope under four soil management practices: mechanical tillage, total artificial protection of soil and soil cover with two different rates of vegetal residues. Overall, they concluded that the retention of vegetal residues over the soil may be advisable to reduce surface runoff generation rates, particularly for saturated soils.…”
Section: Hydrological Properties For Hydrological Model Applications mentioning
confidence: 99%